Reduction in pain intensity, range of motion and serum creatine kinase through manipulation of sport massage - Ilmi, Mochamad Azhar; Setijono, Hari; Roepajadi, Joesoef; Turi, Moh; Putri, Syafira Thalita (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the effect of sports massage manipulation on serum creatine kinase levels, range of motion (ROM), and pain intensity following eccentric activity. Eccentric movements can lead to muscle damage and soreness due to maximal muscle lengthening to generate force, which increases serum creatine kinase, reduces ROM, and intensifies pain. This laboratory experimental study used a randomized pretest-posttest group design involving 30 males aged 21–24 years, divided into five groups: four treatment groups (effleurage, petrissage, shaking, and tapotement) and one control group. Participants performed 10 sets of drop jumps, followed by a 20-minute sports massage administered six hours later. ROM was measured using a goniometer, pain intensity with a visual analogue scale (VAS), and serum creatine kinase levels via laboratory analysis. Results showed a significant increase in knee ROM (p = 0.019) and a significant reduction in pain intensity (p = 0.001) 24 hours after activity. However, no significant change was observed in serum creatine kinase levels (p = 0.525). In conclusion, sports massage manipulation effectively improves ROM and reduces pain following eccentric activity but does not significantly affect serum creatine kinase levels.